Retinal and choroidal microvascular characterization and density changes in different stages of diabetic retinopathy eyes - Wang, Hui; Liu, Xuhui; Hu, Xiaofeng; Xin, Hua; Bao, Han; Yang, Shuo (Frontiers in Medicine, 2023)
Background The purpose of this study was to evaluate the changes in fundus vascular density and micromorphological structure of all vascular plexuses during the different stages of diabetic retinopathy (DR), and the correlation between fundus blood flow and the DR severity. Methods This observational cross-sectional study was conducted of 50 eyes with different stages of DR, 25 diabetes mellitus (DM) patients without clinical signs of DR and 41 healthy eyes. The foveal avascular zone (FAZ), vessel density of superficial capillary plexus (SCP) and deep retinal capillary plexus (DCP) were acquired by RTVue XR Avanti OCTA device. The perfusion density (PD), skeleton vessel density (SVD) was manually calculated using ImageJ. The area under receiver operating characteristic (ROC) curve was used to determine the diagnostic value of OCTA parameters in distinguishing DR and healthy eyes. Results The choroidal VD were significantly higher in the healthy group than in the DM without DR, NPDR and PDR groups (P < 0.001). The mean retinal parafovea VD, PD and retinal SVD were higher in healthy and DM without DR eyes compared with NPDR and DR eyes in all vascular layers (P < 0.001). The parafoveal VD of SCP and DCP decreased, and FAZ area increased with the exacerbation of DR. The OCTA parameters, including FAZ area, parafovea VD, PD and SVD in all vascular layers showed significant correlation with DR severity (all P < 0.001). ROC curves of OCTA parameters (FAZ area, retinal parafovea VD, retinal PD and SVD in all vascular layers) for had high sensitivity and specificity in distinguishing DR versus healthy eyes. Conclusion The choroidal parafovea VD, retinal parafovea VD, retinal PD and SVD in the two plexuses decreased, and retinal FAZ area increased significantly with worsening DR. VD, PD and SVD might be potential early biomarkers indicating the progression of DR before appearance of clinically PDR in patients with DM. In this study, OCTA parameters had high sensitivity and specificity in distinguishing DR and healthy eyes.